POETRY DISGUISED AS LIFE, OR HALYNA KRUK’S WAR DIARY - Golod, Roman (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2026)
The purpose of the article is to study the existential image of the human being in Halyna Kruk’s online poetry and diary. The article examines ideological and thematic aspects, figurative techniques, the peculiarities of the poet’s individual style, and her ability to find relevant artistic forms for expressing anti-militarist motifs in her work. The theoretical and methodological basis of the study consists of works by scholars who have examined the anti-militarist writing of Halyna Kruk (Liudmyla Shumeiko, Olena Saikovska) and the features of the contemporary Ukrainian literary process (Olena Haleta, Artem Chekh). The article employs hermeneutic methods (in interpreting the author’s system of imagery), elements of genre analysis (in determining the genre specificity of the diary), and methods of reception aesthetics (in observing the suggestive influence of Kruk’s works on the reader). The findings show that Halyna Kruk’s work is largely representative in discussions about the directions of contemporary Ukrainian literature under wartime conditions. The ideological and thematic focus of her online poetry and diary—supporting resistance to occupation and preserving the memory of war crimes—corresponds to the historical challenges facing the Ukrainian people during the ongoing catastrophe. Her work contributes to the formation of national identity at the level of the collective subconscious. Distinctive features of the author’s individual style include the realization of thematic content through relevant genre forms and artistic techniques, among them the somewhat “forgotten” realist principle of “depicting life in the forms of life itself.” The article attempts, based on an analysis of Halyna Kruk’s online works, to identify key tendencies in the development of contemporary Ukrainian literature, to clarify the significance of art in general and literature in particular in wartime, and to investigate the genesis of genre and style during years of wartime devastation. The results of the study can be used in scholarly research and academic courses related to the study of Halyna Kruk’s individual authorial style and the genre potential of poetry and diaries within the discourse of anti-militarist literature.